Pengaruh Akuntansi Forensik dan Audit Investigasi terhadap Pengungkapan Kecurangan pada Kantor Akuntan Publik di Jabodetabek - Devina Mutiara Sahilah; Eko Cahyo Mayndarto; Shofia Asry (Lembaga Pengembangan Kinerja Dosen, 2026)
This paper aims to analyze the influence of forensic accounting and investigative auditing on fraud disclosure. This paper uses a quantitative approach with a causality research type. Data were obtained by distributing questionnaires to 80 auditors working at Public Accounting Firms (KAP) in the Greater Jakarta area. The data analysis techniques used were simple and multiple linear regression analysis. The paper shows that forensic accounting has a positive and significant effect on fraud disclosure. Investigative auditing also has a positive and significant effect on fraud disclosure. Simultaneously, both independent variables contribute to the dependent variable, with an Adjusted R² value of 41.6%. This indicates that forensic accounting and investigative auditing together can explain 41.6% of the fraud disclosure variable, with the remainder influenced by other factors in this study. This study implies that the effective implementation of forensic accounting and investigative auditing can improve auditors' ability to detect and disclose fraud. Therefore, business entities and financial auditing institutions are expected to strengthen auditor competencies in both areas to improve financial transparency and accountability.